Sounds of Strength: a programmatic evaluation of a music therapist led community-based program for Veterans in supportive housing - Gooding, Lori F.; Hernandez, Flor del Cielo; Langston, Diane G. (Frontiers in Psychiatry, 2025)
IntroductionComplexities such as TBI and co-occurring conditions such as homelessness impact Veterans’ awareness and use of health care services offered in the VHA and the community. Thus, targeted interventions that engage and reduce barriers to care among Veterans with interconnected challenges are needed. Research has suggested that music therapy interventions are well received by both active-duty Service Members and Veterans, but little is available on music therapy-based programming to address the complex needs of Veterans with interconnected challenges.MethodsThe purpose of this project was to conduct a programmatic evaluation of a music therapist-led, community-based music program offered in a supportive housing complex to foster mental, emotional, and social health and wellbeing in Veterans encountering long-term and repeated homelessness, TBI, and other co-occurring conditions. We reviewed music therapist notes, attendance logs, participant demographic data, and unsolicited feedback from a 45-session music program grounded in a whole health and trauma-informed perspective to (a) identify the music interventions used and (b) explore how Veterans perceived the program. Demographic and attendance data were analyzed descriptively, and therapist notes and unsolicited feedback were examined thematically.ResultsResults showed Veterans preferred rock, country, blues, and folk music, and singing and instrument play were the most common music strategies implemented in the program. Session topics most often included music, recreation/leisure, and emotions. The most common therapist objectives included self-expression, building rapport, and group cohesion. Both therapist notes and Veteran comments suggested that the program was appreciated, and it created a space where challenges could be addressed.ConclusionThis is one of the first music therapy programs presented in the literature to focus on Veterans experiencing homelessness and living in supportive housing. Results suggest that music therapy programming may be an innovative, well received option to engage Veterans with interconnected challenges. Results further suggest that sessions offered directly in supportive housing units and collaborating with Veterans on music planning may build trust and connection and empower them to take charge of their own health and wellbeing. Thus, music therapy-based programming may be uniquely positioned to address the needs of this marginalized population.